Conditional antecedents containing the German discourse particle denn - Zobel, Sarah (Linguistica (Ljubljana), 2016)
We discuss the semantic contribution and distribution of conditional antecedents containing the discourse particle denn ("antecedents with denn", abbreviated as AWD). We propose that AWDs occur only in contexts where (i) the speaker does not believe the antecedent proposition p to hold, and (ii) the truth of p has been nonexplicitly (= tacitly) proposed. To gain a better understanding of (ii), we conduct two corpus studies. The first study investigates the relative location of AWDs with respect to their consequents. We find that unlike antecedents of regular hypothetical conditionals, AWDs occur significantly more often after the material in the consequent and parenthetically inside this material than before it. In a second study, we investigate the position of the tacit proposal relative to the AWD. We find that it typically precedes the AWD. Both results are in accordance with (ii). We then present a classification of the types of tacit proposals that we find with AWDs: speakers use AWDs to qualify their own statements or to doubt proposals of others, in both cases managing potential updates to the common ground.
Keywords: allemand; Corpus linguistics; členek; diskurzivni členek; German; korpusna lingvistika; linguistique de corpus; nemščina; particule; particule discursif; pogojni odvisnik; semantics; semantika; sémantique; skladnja; subordonnée de condition; syntax; syntaxe